Al2O3/MC particles reinforced MoFeCrTiWNbx high-entropy-alloy coatings prepared by laser cladding. (1st February 2022) - Kuang, Shihua; Zhou, Fang; Liu, Wencheng; Liu, Qibin
ABSTRACT: The Al2 O3 /MC particles reinforced MoFeCrTiW(Al2 O3 )0.5 Nb x ( x  = 1, 1.5, 2, 2.5, and 3) high-entropy alloy coatings were successfully fabricated on the M2 high-speed steel by laser cladding. An investigation was carried out to assess the effect of the Nb on the microstructure and properties of coatings. The coatings are all composed of the BCC solid-solution phase, C14-Laves phase, and (Nb, Ti)C carbide plus a small amount of Al2 O3 . An increasing in Nb content results in the microstructural change from hypoeutectic to eutectic and the improvement in the hardness and wear resistance of the coating. When x  = 3, the coating possesses the highest hardness (∼782 HV0.2 ) and lowest wear volume loss (∼0.52 mm 3 ). The dispersion strengthening and lamellar boundary strengthening play a dominating role in enhancing the hardness and wear resistance of coatings.